THE IMPACT OF CONSUMER DECISIONS IN PURCHASING FOODS BASED ON PRICE, PRODUCT DESIGN, LOCATION, AND STORE ATMOSPHERE - Hendarto, Totok; Ermaini, Ermaini; Fatmawati, Endang; Ismanto, Widodo; Wibowo, Teguh Setiawan; Tsai, Chia Han (Universitas Brawijaya, Indonesia, 2023)
In the world of business competition, entrepreneurs are demanded to be able to respond and act quickly to face increasingly fierce business competition within the scope of one location. Entrepreneurs are expected to be able to compete healthily and competitively to create the most exciting innovations to maintain their loyalty. Each entrepreneur will make every effort to influence the buyer's decision by consumers so that they are interested in the products they market. This explanatory research uses primary data collected from respondents to be processed through SPSS, data and statistical application. In this study, the objects are the relationship between price, product design, location, store atmosphere, and consumer decisions. The subject of this research is a Culinary Cafe located in Malang City. The sampling technique used is purposive sampling, and the sample obtained is 100 respondents. The data analysis used is descriptive statistics, and multiple regression is used to test the hypothesis in this study. The results show that the variables of price, product design, and location significantly affect purchase decisions, while store atmosphere has no significant effect on purchase decisions. And from the simultaneous test results, the four independent variables together affect purchase decisions at Culinary Cafes in Malang City. Companies can use the implications of this research to make decisions to attract consumers to make purchases.